2007
DOI: 10.1158/1078-0432.ccr-07-0674
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Targeted T Cells Eradicate Systemic Acute Lymphoblastic Leukemia Xenografts

Abstract: Purpose: HumanTcells targeted to the B cell^specific CD19 antigen through retroviral-mediated transfer of a chimeric antigen receptor (CAR), termed 19z1, have shown significant but partial in vivo antitumor efficacy in a severe combined immunodeficient (SCID)-Beige systemic human acute lymphoblastic leukemia (NALM-6) tumor model. Here, we investigate the etiologies of treatment failure in this model and design approaches to enhance the efficacy of this adoptive strategy. Experimental Design: A panel of modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
341
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(361 citation statements)
references
References 34 publications
9
341
1
3
Order By: Relevance
“…This reduction in IL-2 production was even more pronounced when CD58 was blocked on the Nalm-6 cell line (Figure 2d) potentially due to the lack of CD80/CD86 co-stimulatory molecules expressed by this tumour line. 12 In contrast to mouse T cells, the addition of the CD28-signalling domain into the CAR induced an enhanced level of IL-2 production as compared with aCD19z T --cells, which could be partially reduced through CD58 blockade (Figure 2e). To extend these observations, aCD19z and aCD19CD28z CAR T cells from five donors were co-cultured with Raji or Nalm-6 cell lines in the presence of anti-CD58 or isotype control antibodies.…”
Section: Resultsmentioning
confidence: 94%
“…This reduction in IL-2 production was even more pronounced when CD58 was blocked on the Nalm-6 cell line (Figure 2d) potentially due to the lack of CD80/CD86 co-stimulatory molecules expressed by this tumour line. 12 In contrast to mouse T cells, the addition of the CD28-signalling domain into the CAR induced an enhanced level of IL-2 production as compared with aCD19z T --cells, which could be partially reduced through CD58 blockade (Figure 2e). To extend these observations, aCD19z and aCD19CD28z CAR T cells from five donors were co-cultured with Raji or Nalm-6 cell lines in the presence of anti-CD58 or isotype control antibodies.…”
Section: Resultsmentioning
confidence: 94%
“…4 In chronic lymphocytic leukemia, a disease that can be subdivided into two subgroups based on a SHM threshold of 2%, AICDA expression is found in both subgroups, although more frequently in cases with o2% SHM. 5 We have recently shown that the IGH gene repertoires and SHM patterns of HCL-variant are more similar to that of SMZL than of typical HCL. 6 There has been only one report so far on AICDA mRNA expression in HCL, which found eight of nine cases to express this gene.…”
mentioning
confidence: 95%
“…CARs against CD19 have now been generated by various groups and have been demonstrated to mediate potent T-cell effector functions against CD19-expressing malignant cells in vitro and in vivo. 5 Specifically, human T cells endowed with CD19-specific CARs have been shown to effectively eradicate human CD19 þ tumor xenografts in immuno-deficient mouse models. 5 So far, in vivo evidence for the antileukemia activity of CD19-specific T cells has been restricted to established tumor cell lines.…”
mentioning
confidence: 99%
See 2 more Smart Citations